Increased flexibility in childcare arrangements: Impacts on parents' careers and children's school performance - Caroline King Barnard Hall; Erica Lindahl; Sara Roman (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
We study the effects of access to a child home care allowance on parents' labor supply and childcare decisions, as well as their longer-term earnings trajectories and children's school performance. To establish causality, we exploit variation in the availability of the allowance over time and across municipalities. The analysis is based on rich administrative data for the entire Swedish population. Our results suggest a negative impact of benefit eligibility on mothers' labor supply and earnings as well as on children's enrollment in childcare during the time the family is entitled to the benefit (until the child turns 3 years old). Negative impacts on mothers' earnings persist after benefit eligibility has expired and are still visible 7 years after childbirth. These effects are driven by mothers who lacked earnings before childbirth, while there are no lasting impacts for mothers with prior employment. We find no effects on fathers' earnings. As for the children, our results suggest that access to the home care allowance had a negative impact on boys' scores on standardized tests at age 10, while there are no significant effects on girls' test scores.
Keywords: J13; J18; J24; 330; Home care allowance; labor supply; earnings; childcare; preschool; school performance